Efeitos da imuno-senescência na infecção murina pelo Schistosoma mansoni - Rafael Pires de Oliveira (2010)
The immunosenescence is defined as a cumulative result of decline in the activity of the immune system activity due to progressive aging, and contributes to increased susceptibility to infectious diseases, cancer and autoimmunediseases. Such aging-related changes include thymic involution, changes in frequencies of activated lymphocytes, in cytokine profile and in lymphocyte repertoire. Generally, aged animals and humans show a reduction in the frequency of naïve T lymphocytes, increased proportion of memory T cells and a diminished immune reactivity to novel antigens. Many studies report changes in the prevalence and intensity of parasitic diseasesduring aging. There is a strong association between age and resistance to infectious diseases, such as schistosomiasis, an endemic disease that affects more than two hundred million people in developing countries. It is possible that the lower infection intensity observed in adults results from the acquisition of protective immunity due to chronic antigenic stimulation. The aim of this work was to evaluate the influence of aging in immune reactivity to infection by Schistosoma mansoni in the mouse. We observed that aged C57BL/6 mice have a reduced inflammatoryresponse to parasite antigens, resulting in lower specific antibody titles. Despite the reduced humoral immune response, old animals were as susceptible to infection as young animals, and they also develop protective immunity against reinfection. Eosinophils activity seemed to be conserved in aged infected animals and may have contributed to worm elimination during reinfection. It is plausible that the altered cytokine balance during disease development changes the dynamics of the granuloma formation/involution in aged mice. Aged mice formed smaller granulomas at acute phase of infection, but they did not develop the process of immunomodulation inchronic phase, as described in young animals. After infection, young mice showed a typical increase in the frequency of activated T cells. On the other hand, we found increased frequencies of activated T cells in non-infected aged mice regardless of their infection status. Lymphocytes in non-infected aged animals were constitutively activated and it is likely that inflammatory responses to novel antigens may be impaired when facing an immune system already highly populated by effector cells.